2019
DOI: 10.1016/j.jpsychires.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of hormonal and social environments in understanding body image concerns in adolescent girls

Abstract: During adolescence, peer approval becomes increasingly important and may be perceived as contingent upon appearance in girls. Concurrently, girls experience hormonal changes, including an increase in progesterone. Progesterone has been implicated in affiliative behavior but inconsistently associated with body image concerns. The current study sought to examine whether progesterone may moderate the association between perceived social pressures to conform to the thin ideal and body image concerns. Secondary ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…The presence of stronger hormone effects in the BE subsample in this study parallels results from a previous study that did not examine individual differences in negative affect (Klump et al, 2014) and suggests that women with a history of clinically significant binge eating may be particularly sensitive to ovarian hormone influences. Although prior studies across the menstrual cycle have suggested that progesterone increases emotional eating by counteracting the protective effects of estradiol (Klump, Keel, Racine, et al, 2013), findings from this study are consistent with recent evidence that progesterone may also strengthen the influence of psychosocial risk factors for disordered eating (e.g., weight-based teasing; Forney et al, 2019). The combination of sustained high negative affect and a within-persons peak in progesterone may therefore be a "perfect storm" for dysregulated eating in women with a history of BEs, who may also be more likely to have other sources of biological or behavioral risk (e.g., a history of dieting) that potentiate these effects.…”
Section: Discussionsupporting
confidence: 89%
“…The presence of stronger hormone effects in the BE subsample in this study parallels results from a previous study that did not examine individual differences in negative affect (Klump et al, 2014) and suggests that women with a history of clinically significant binge eating may be particularly sensitive to ovarian hormone influences. Although prior studies across the menstrual cycle have suggested that progesterone increases emotional eating by counteracting the protective effects of estradiol (Klump, Keel, Racine, et al, 2013), findings from this study are consistent with recent evidence that progesterone may also strengthen the influence of psychosocial risk factors for disordered eating (e.g., weight-based teasing; Forney et al, 2019). The combination of sustained high negative affect and a within-persons peak in progesterone may therefore be a "perfect storm" for dysregulated eating in women with a history of BEs, who may also be more likely to have other sources of biological or behavioral risk (e.g., a history of dieting) that potentiate these effects.…”
Section: Discussionsupporting
confidence: 89%
“…This might be caused by the fact that during the premenstrual phase women exhibit a distortion of the perception of their body image, which results, for example, in perceiving an increase in body size 56 , 57 , an overestimation of waist size 58 or to a higher focus on unattractive body parts 59 . This distortion might be caused by higher levels of progesterone during the premenstrual phase, which are proved to cause higher body image concerns 60 . The body image dissatisfaction during the premenstrual phase could also be explained by interoceptive and physical symptoms such as bloating, breast tenderness and fluid retention 93 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, research has demonstrated that associations between ovarian hormones and other ED symptoms may differ according to the environmental context. For example, Forney and colleagues [ 90 ] found that progesterone levels were associated with body image concerns in girls, but only in the presence of other psychosocial stressors (e.g., weight-related teasing).…”
Section: Reproductive Age: Dynamic Activational Hormone Effectsmentioning
confidence: 99%